Analisis Hukum terhadap Hukuman Kebiri Bagi pelaku Kekerasan Seksual Terhadap Anak Berdasarkan Peraturan Pemerintah No. 70 tahun 2020 - Sonya Airini Batubara; Cindy Cynthia Leoni; Ferry Salim; Frans Deo Fanny Sinaga (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Chemical castraction is done by injecting a person’s body containing chemical compuds in the form of anti-androgens so that production of the hormone testosterone decreases, so that sexual desire decreases. In the medical world, the hormone testosterone is a hormone that is very functional for male sexuality, if these chemical compounds enter the male vital organs, the compunds block the braind grlands so that no longer produce testosterone, and can reduce libido. The perpetrator of the first castraction sentence in Indonesia is Muhammad Aris he is 20 years old and has raped nine minors. Aris was sentenced to imprisonment for 12 years on May 2, 2019. With this incident, researchers are interested in citing the Legal Analysis of Sentce of Castraction for Perpetrators of Violence Againts Children Based on Government Regulation No. 70 of 2020. Formulation of the problem How to apply caism or castraction punishment in Indonesia in acts of violence Criminal acts of Violence Againts Children based on PP/70/2020 related to Chemical Castraction Methods, Placement of Electronic Detection Devices, Healing and Identity Development of Sexual Perpetrators against children? The Perspective of Human Rights (HAM) in the law of castraction against predators of child sexual violence based on PP/70/2020 regarding Methods of Implementing Chemical Castraction, Placement of Electronic Detection Devices, Healing, and Announcement of the Identity of Perpessstrators of Violence against children. The theory used in this paper is the theory of legal protection of legal legal protection. Research conducted by Library Research, using the inductive deductive method, the concludions drawn are correct. Based on the research conducted, it is known that chemical castration is by injecting it into the human body to reduce or even lose lust. These actions certainly violate human nature and make the perpetrators actually become termonted. The validity of the sentence is considered to have no humanity because it has violated the perpetrator. Legal expert, helath expert, and human rights activist support the law because sexual.